Ivan Goncharov as a participant of negotiations with the Japanese (based on materials from the Russian State Archive of the Navy) - Alexey Balakin (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
The article is devoted to the activities of Ivan Goncharov as a participant of the expedition under command of Adjutant General, Vice Admiral E.V. Putyatin, who provided material for the book of essays “Frigate ‘Pallada’”. Emphasis is made on the writer’s participation in the 1853 negotiations with Japan as a secretary and author of a significant part of official reports sent to St. Petersburg, as well as other documents of a diplomatic nature. For the first time, materials currently stored in the Russian State Archive of the Navy are being introduced into scientific circulation. First of all, these are the diplomatic documents of the expedition in the file “On the instructions given to Adjutant General Putyatin when sending him on a voyage around the world on the frigate “Pallada” concerning the establishing of political and commercial ties between Russia and Japan, etc.”, which highlight the details of negotiations with the Japanese authorities. A detailed description of these documents (letters, diplomatic dispatches, reports, etc.), partially published as part of the article, is given as well as their comparison with other sources, including notes by Archimandrite Avvakum, who participated in the expedition as a translator. The materials included in the article can significantly complement both the documentary and creative history of Goncharov’s essays “Frigate ‘Pallada’”, as well as the chronicle of the writer’s life and work as a whole. Thus, documents first published by the author of the article reveal an important aspect of Goncharov’s activity as not only a writer, but also a participant of a diplomatic mission.